2012
DOI: 10.1159/000339937
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin Pharmacokinetics and Pharmacodynamics during Short-Daily Hemodialysis

Abstract: Background/Aims: Gentamicin pharmacokinetics have not been described in patients undergoing short-daily hemodialysis (SDHD). The aim of this study is to describe gentamicin pharmacokinetics and dialytic clearance (Cldial) in SDHD patients and simulate gentamicin exposure after six dosing regimens to help guide future dosing. Methods: Six anuric patients undergoing SDHD were enrolled. Patients received intravenous infusion of 2 mg/kg gentamicin on day 1 after the first HD session followed by HD sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
(22 reference statements)
2
11
0
Order By: Relevance
“…However, large evolutionary steps in membrane materials, such as the step from diacetate membranes such as the Baxter CAHP family to intermediate flow triacetate membranes as the Nipro Sureflux-E and the next step to high flow triacetate membranes such as the Nipro Sureflux-UX (SFUX) family have caused considerable impact on clearance rates, as is shown in Figure 3 . Similar to Decker et al we found overall considerably increased clearance values compared to previous publications ( Decker et al, 2012 ). However, due to the larger membrane area of the dialyzers used in our trial the clearance rates presented in this manuscript are even higher, further supporting administration of high doses of aminoglycosides pre dialysis and complete removal of the drug during hemodialysis, thus reducing toxicity ( Decker et al, 2012 ; Veinstein et al, 2013 ; Vossen and Thalhammer, 2013 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, large evolutionary steps in membrane materials, such as the step from diacetate membranes such as the Baxter CAHP family to intermediate flow triacetate membranes as the Nipro Sureflux-E and the next step to high flow triacetate membranes such as the Nipro Sureflux-UX (SFUX) family have caused considerable impact on clearance rates, as is shown in Figure 3 . Similar to Decker et al we found overall considerably increased clearance values compared to previous publications ( Decker et al, 2012 ). However, due to the larger membrane area of the dialyzers used in our trial the clearance rates presented in this manuscript are even higher, further supporting administration of high doses of aminoglycosides pre dialysis and complete removal of the drug during hemodialysis, thus reducing toxicity ( Decker et al, 2012 ; Veinstein et al, 2013 ; Vossen and Thalhammer, 2013 ).…”
Section: Discussionsupporting
confidence: 90%
“…52,53 Table 2 summarizes recent PK studies and considerations for a starting point for dosing commonly used antimicrobials in patients receiving PIRRT. 54-78 The supplemental materials discuss the literature in detail for each individual drug.…”
Section: Drug Dosing Updates For Ihd Pirrt and Crrtmentioning
confidence: 99%
“…Therefore, administering an aminoglycoside prior to dialysis should theoretically allow the achievement of a high peak concentration (thereby enhancing bacterial killing), while subsequent early dialytic clearance should help to minimize the AUC and trough concentrations (thereby limiting toxicity) [32]. However, this point is controversial in the literature, where the Renal Drug Handbook [30] and the Kidney Disease Program [31] advise to administer aminoglycosides after dialysis, presumably based on older studies [33], and more recent studies indicate that aminoglycosides should be administered prior to dialysis [34, 35]. Unfortunately, for most patients with renal impairment, also with RRT, attaining both adequate peak and trough concentrations is unlikely.…”
Section: Pharmacokinetics and Pharmacodynamics Of Anti-infective Agenmentioning
confidence: 99%